Knowledge regarding HIV/AIDS and its prevention among high school students of Anantnag district, Jammu and Kashmir, India: a pre-experimental study - Reyaz, Munaza; Shil, Rahul (International Journal Of Community Medicine And Public Health, 2024)
Background: India has become one of the most populous country in the world, and it would be a disaster if our adolescent children fell into the trap of HIV/AIDS, which not only disrupts the healthcare system of any country but also has an impact on the morals of the people. Therefore, the main aim of the study was to understand the knowledge regarding HIV/AIDS and its prevention among high school children. Methods: This was a pre-experimental study in which 60 high school students participated. The knowledge was assessed using demographic characteristics and 30-item knowledge questionnaires. SPSS V16.0 was used for the data analysis. Paired t-test, descriptive statistics, and chi-square analysis were used to check the association. Results: In the study, the majority of the participants, 46 (76.66%), had inadequate knowledge, and only 14 (23.33%) had moderate knowledge regarding HIV/AIDS. The paired “t”-test value was 54.63 at the level of p<0.0001, which was significant. We also found multiple associations between gender, qualification of the mother, occupation of the mother, qualification of the father, occupation of the father, type of family, and source of information. Conclusions: It was observed that there was relatively less knowledge among high school students regarding HIV/AIDS and its prevention. However, after the teaching program, the knowledge improved. Therefore, a multi-dimensional approach should be taken by the school authority to create awareness campaigns for the students.